Preoperative Posterior Tilt Increases the Risk of Later Conversion to Arthroplasty After Osteosynthesis for Femoral Neck Fracture - Honkanen Jukka S; Ekman Elina M; Huovinen Ville K; Mäkelä Keijo T; Koivisto Mari; Karvonen Mikko P; Laaksonen Inari (Elsevier, 2022)
Background
Femoral neck fractures (FNFs) are one of the most common injuries in the elderly. Treatment is either internal fixation or primary arthroplasty. The main aim of this study is to assess the risk factors associated with fixation failure leading to further arthroplasty in FNFs treated with cannulated screws.
Methods
Data on internal fixations of FNFs performed at Turku University Hospital between January 1, 2012 and December 31, 2017 were collected retrospectively from the patient database. Radiographical measurements were performed for preoperative displacement and posterior tilt, postoperative displacement, reduction quality, and implant shaft angle.
Results
Altogether 301 cases were included in the study. The overall reoperation rate was 25% and conversion to arthroplasty was performed in 16% of cases. In the multiple variant analysis, adjusted for age and gender, nondisplaced fractures with a 0°-20° preoperative posterior tilt had a significantly lower risk of later conversion to arthroplasty than did nondisplaced fractures with a ≤0° or ≥20° posterior tilt (odds ratio [OR] 4.0, 95% confidence interval [Cl] 1.8-8.6, P = .0005) and displaced fractures (OR 7.2, 95% CI 3.0-17.4, P < .0001). No statistically significant association was found between preoperatively nondisplaced fractures with a <0° or ≥20° posterior tilt and displaced fractures (OR 0.6, 95% Cl 0.2-1.3, P = .2).
Conclusion
Displaced fractures and fractures with a preoperative posterior tilt of <0° or ≥20° have a considerably increased risk of reoperation and conversion to arthroplasty. Primary arthroplasty should be considered as treatment for displaced FNFs and fractures with >20° or <0° posterior tilt, especially in fragile patients, to avoid further operations.
Keywords
internal fixation
arthroplasty
reoperation
fixation failure
posterior tilt
femoral neck fracture